First record of the subfamily Brachycyrtinae (Hymenoptera, Ichneumonidae) from continental Africa, with description of three new species - Giovanni, Filippo Di; Varga, Oleksandr (Zootaxa, 2021)
The genus Brachycyrtus is recorded for the first time from continental Africa. Three new species are described: Brachycyrtus antoninoi sp. n., B. cerrettii sp. n., and B. lucchii sp. n. A key to distinguish the newly described taxa is provided.